Normal Fetal Lumbar Spine on Postmortem MR Imaging - Widjaja, E.; Whitby, E.H.; Paley, M.N.J.; Griffiths, P.D. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: There is an increasing interest in use of postmortem MR imaging as an adjunct or alternative to autopsy. Before evaluating spinal pathology on postmortem MR imaging, it is important to have knowledge of the normal appearance of the fetal spine at different gestational ages. The aim of this study is to describe the MR imaging appearances of normal development of the fetal spine at different gestational ages.METHODS: Postmortem MR imaging was performed on 30 fetuses ranging from 14 to 41 gestational weeks. There was no structural abnormality of the spine in these fetuses on MR imaging or at autopsy. Fast spin-echo T2-weighted MR imaging of the lumbar spine was performed in the coronal plane in all cases and supplemented by sagittal and/or axial imaging. The following parameters were measured: height of the L1/2 disk and L2 vertebral body and area of ossification center in L2 vertebral body as well as area of vertebral body. The signal intensity of the disk space and the vertebral level of conus termination were also assessed.RESULTS: The height and area of the vertebral body increased linearly with gestational age (P <.01). The increase in disk space was proportionally greater than the increase in vertebral body height as gestational age increased (P <.01). The disk space appeared as a linear low-signal-intensity area in fetuses ≤21 weeks gestation but increasingly developed high signal intensity in the disk after 21 weeks. The size of the ossification center increased with gestational age (P <.01), and the ratio of ossification center to the overall size of the vertebral body also increased with gestational age (P <.01). In fetuses less than 35 weeks of age, the conus lay between L2 and L5 level, whereas in fetuses more than 35 weeks of age, the conus lay between L1/2 and L2/3 level.CONCLUSION: Understanding the normal growth and signal-intensity characteristics of the fetal spine on postmortem MR imaging is essential before studying abnormal fetal spine.